Direct electrooxidation of alkynes to benzoin bis-ethers. Issue 24 (5th November 2020) - Yang, Zengzhuan; Lu, Fangling; Li, Haiyan; Zhang, Yuying; Lin, Wen; Guo, Peng; Wan, Juelin; Shi, Renyi; Wang, Tao; Lei, Aiwen
Abstract : Electrosynthesis of benzoin bis-ethers from alkynes and alcohols under metal-free and external oxidant free conditions. Abstract : A direct electrochemical oxidation of alkynes for the synthesis of benzoin bis-ethers has been developed. Various alkynes and alcohols are compatible, generating the desired products in up to 85% yield. This transformation can be performed under mild reaction conditions in the absence of an external oxidant and transition metal catalyst. Preliminary mechanism studies suggest that the product carbonyl oxygen originated from water.